2018
DOI: 10.1116/1.5044643
|View full text |Cite
|
Sign up to set email alerts
|

Gas-cluster ion sputtering: Effect on organic layer morphology

Abstract: Analysis of the surface of thin Irganox 1010 films before and after sputtering with an argon gas-cluster ion beam was performed with AFM and XPS to determine the effect that Zalar rotation has on the chemistry and morphology of the surface. The analysis is based on the change in roughness of the surface by comparing the same location on the surface before and after sputtering. The ion beam used was an of size= 1000 and energy 4 keV. The XPS analysis agreed with previous results in which the ion beam did not ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…76,77 To circumvent some limitations posed by monatomic ion etching, one can use a more 'gentle' sputtering technique such as argon cluster ion (Ar n + ) or C 60 sputtering. [78][79][80] Gas cluster ion sputtering (GCIS), as the technique is commonly known, can be quite often found as an option on modern XPS instruments. While there are so far few examples for the use of GCIS in battery research, it offers promise due to its ability to sputter etch soft materials without leaving much chemical damage.…”
Section: Ion Sputter Etchingmentioning
confidence: 99%
“…76,77 To circumvent some limitations posed by monatomic ion etching, one can use a more 'gentle' sputtering technique such as argon cluster ion (Ar n + ) or C 60 sputtering. [78][79][80] Gas cluster ion sputtering (GCIS), as the technique is commonly known, can be quite often found as an option on modern XPS instruments. While there are so far few examples for the use of GCIS in battery research, it offers promise due to its ability to sputter etch soft materials without leaving much chemical damage.…”
Section: Ion Sputter Etchingmentioning
confidence: 99%
“…The surface of these shadows was relatively smooth, as shown in Figure S2 in the SI. Sputtering-induced roughness has been reported in both organic 39 and inorganic materials. 40,41 For example, Conard 40 has shown that the bombardment of the Ar n + cluster can cause the development of surface roughness on the aluminum delta layers, particularly in the early stage of the sputtering process, which was also predicted using molecular dynamics simulations.…”
Section: Resultsmentioning
confidence: 99%
“…All atomic force microscope (AFM) images were gathered with a Multimode IV (currently Bruker, formerly Digital Instruments, Camarillo, CA, USA) AFM. To determine the GCIS effect directly, AFM images were gathered at the same position on the film before and after sputtering; this was done by using the pattern on the back of the glass slide to orient the sample as well as micron-scale details on the surface, see reference [28] for more information. Imaging the same spot was crucial to analyze the morphological changes as a result of GCIS directly.…”
Section: Methodsmentioning
confidence: 99%
“…The PAni films were measured to be 69.9 ± 0.3 nm thick as measured by AFM in the method described elsewhere [28,37]. The samples were then thinned to 59.3 ± 0.5 nm by GCIS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation